89Zr-anti-γH2AX-TAT but not 18F-FDG allows early monitoring of response to chemotherapy in a mouse model of pancreatic ductal adenocarcinoma - Knight, J; Mosley, M; Contreras Bravo, L; Kersemans, V; Allen, D; Mukherjee, S; O'Neill, >; Cornelissen, B (American Association for Cancer Research, 2017)
Purpose: Late-stage, unresectable pancreatic ductal adenocarcinoma (PDAC) is largely resistant to chemotherapy and consequently has a very poor 5-year survival rate of < 5%. The ability to assess the efficacy of a treatment soon after its initiation would enable rapid switching to potentially more effective therapies if the current treatment is found to be futile. We have evaluated the ability of the PET imaging agent, 89Zr-anti-γH2AX-TAT, to monitor DNA damage in response to fluouracil (5-FU), gemcitabine, or capecitabine treatment in a mouse model of pancreatic cancer. We have also compared the utility of this approach against the standard clinical PET radiotracer, 18F-FDG. Experimental Design: C57BL/6 mice bearing subcutaneous pancreatic cancer (KPC; B8484) allografts were treated with 5-FU, gemcitabine, or capecitabine. Therapeutic response was monitored by positron emission tomography and ex vivo biodistribution experiments using either 89Zr-anti-γH2AX-TAT or 18F-FDG as imaging agents. To further examine the effect of therapeutic response upon uptake of these imaging agents, immunohistochemical analysis of harvested tumour allograft tissue was also performed. Results: Accumulation of 89Zr-anti-γH2AX-TAT in the tumours of mice that received chemotherapy was higher compared with vehicle-treated mice and was shown to be specifically mediated by γH2AX. In contrast, 18F-FDG did not provide useful indications of therapeutic response. Conclusions: 89Zr-anti-γH2AX-TAT has shown a superior ability to monitor early therapeutic responses to chemotherapy by PET imaging compared with 18F-FDG in an allograft model of PDAC in mice.